2010
DOI: 10.1152/ajprenal.00374.2010
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated potassium channel Kv1.3 blocker as a potential treatment for rat anti-glomerular basement membrane glomerulonephritis

Abstract: The voltage-gated potassium channel Kv1.3 has been recently identified as a molecular target that allows the selective pharmacological suppression of effector memory T cells (T(EM)) without affecting the function of naïve T cells (T(N)) and central memory T cells (T(CM)). We found that Kv1.3 was expressed on glomeruli and some tubules in rats with anti-glomerular basement membrane glomerulonephritis (anti-GBM GN). A flow cytometry analysis using kidney cells revealed that most of the CD4(+) T cells and some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 62 publications
2
35
1
Order By: Relevance
“…In addition, specific Kv1.3 inhibitors have been found to be effective in numerous animal models of inflammation including chronic relapse-remitting experimental autoimmune encephalomyelitis (CR-EAE) and adoptive EAE (Beeton et al, 2005(Beeton et al, , 2006, pristane-induced arthritis (PIA) (Beeton et al, 2006), the delayed-type hypersensitivity (DTH) reaction (Koo et al, 1997;Beeton et al, 2005;Matheu et al, 2008), allergic contact dermatitis (Azam et al, 2007), allogeneic kidney transplant (Grgic et al, 2009), spontaneous autoimmune diabetes (Beeton et al, 2006), vascular neointima hyperplasia (Cheong et al, 2011), antiglomerular basement membrane glomerulonephritis (Hyodo et al, 2010), and psoriasis (Gilhar et al, 2011). For these reasons, numerous groups have focused on developing specific and potent inhibitors of the Kv1.3 channel for the treatment of inflammation and autoimmune disease Chandy 2009, Rangaraju et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, specific Kv1.3 inhibitors have been found to be effective in numerous animal models of inflammation including chronic relapse-remitting experimental autoimmune encephalomyelitis (CR-EAE) and adoptive EAE (Beeton et al, 2005(Beeton et al, , 2006, pristane-induced arthritis (PIA) (Beeton et al, 2006), the delayed-type hypersensitivity (DTH) reaction (Koo et al, 1997;Beeton et al, 2005;Matheu et al, 2008), allergic contact dermatitis (Azam et al, 2007), allogeneic kidney transplant (Grgic et al, 2009), spontaneous autoimmune diabetes (Beeton et al, 2006), vascular neointima hyperplasia (Cheong et al, 2011), antiglomerular basement membrane glomerulonephritis (Hyodo et al, 2010), and psoriasis (Gilhar et al, 2011). For these reasons, numerous groups have focused on developing specific and potent inhibitors of the Kv1.3 channel for the treatment of inflammation and autoimmune disease Chandy 2009, Rangaraju et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, the authors also demonstrated the therapeutic efficacy of a Kv1.3-channel inhibitor, PAP-1, in dextran sodium sulfate (DSS)-induced rat models of ulcerative colitis [90] (Table 1). In experimental animal models of renal diseases, including renal allograft rejection [91] and acute glomerulonephritis [92], immunosuppression by the blockade of lymphocyte Kv1.3-channels actually prevented or ameliorated the progression of the diseases. Using selective Kv1.3-channel inhibitors, such as ShK and Psora-4, therapeutically [91,92], these studies demonstrated the contribution of the channels to the pathogenesis of renal diseases (Table 1).…”
Section: Targeting Lymphocyte Kv13 In ''Chronic Inflammatory Diseases''mentioning
confidence: 99%
“…In experimental animal models of renal diseases, including renal allograft rejection [91] and acute glomerulonephritis [92], immunosuppression by the blockade of lymphocyte Kv1.3-channels actually prevented or ameliorated the progression of the diseases. Using selective Kv1.3-channel inhibitors, such as ShK and Psora-4, therapeutically [91,92], these studies demonstrated the contribution of the channels to the pathogenesis of renal diseases (Table 1). Recently, using a rat model with advanced chronic renal failure (CRF), we demonstrated for the first time that Kv1.3-channels were overexpressed in proliferating leukocytes within fibrotic kidneys [61].…”
Section: Targeting Lymphocyte Kv13 In ''Chronic Inflammatory Diseases''mentioning
confidence: 99%
See 1 more Smart Citation
“…The central memory T cell (Tcm) population (CD45RC-CCR7+ [21,36]) was increased in graft infiltrating CD4+ and CD8+ T cells after i.p. and local correolide C treatment as compared with controls (Fig.…”
Section: Phenotype Of T Cells and Presence Of Memory T Cellsmentioning
confidence: 99%